Synthesis Of 2-Benzamidomethyl-5-Substituted Amino-1,3,4-Thiadiazoles-2,5-Disubstituted 1,3,4-Oxadiazole and 4,5-Disubstituted 1,2,4-Triazole-3-Thiol - K. M. Daoud; A. N. Ali; A. A. Ahmed (College of Education for Pure Sciences, 2012)
Abstract In this paper the synthesis of some substituted 1,3,4-oxadiazoles , 1,3,4-thiadiazoles and 1,2,4-triazoles starting from amino acid and benzoyl chloride is reported. Treatment of glycine or alanine with benzoyl chloride in presence of sodium carbonate gave keto-acid(1,2), which were converted to oxazolinone (3,4) by their reaction with acetic anhydride. Oxazolinone (3,4) were treated with hydrazine hydrate to give acid hydrazides (5,6). Acid hydrazides were converted to substituted thiosemi- carbazides (7,8) by their reaction with phenyl isothiocyanate. Substituted thiosemicarbazides (7,8) were treated with sodium hydroxide and concentrated sulphuric acid give substituted 1,2,4-triazoles (9,10), 1,3,4-thiadiazoles (11,12) respectively while treatment of (7) with mercuric oxide gave 1,3,4-oxadiazoles (13). Treatment of triazoles (9,10) with 4-hydroxybenzaldehyde gave substituted triazoles (14,15). 1-Substituted thiosemicarbazide (16) was obtained from acid hydrazide (5), cyclized with sodium hydroxide to 5-Substituted-1,2,4-triazole-3-thiol (17). The structures of the synthesized compounds were confirmed by physical and spectral means.